Two-dimensional hybrid layered materials: strain engineering on the band structure of MoS2/WSe2 hetero-multilayers. (14th August 2017) - Gu, Kunming; Yu, Sheng; Eshun, Kwesi; Yuan, Haiwen; Ye, Huixian; Tang, Jiaoning; Ioannou, Dimitris E; Xiao, Changshi; Wang, Hui; Li, Qiliang
Abstract: In this paper, we report a comprehensive modeling and simulation study of constructing hybrid layered materials by alternately stacking MoS2 and WSe2 monolayers. Such hybrid MoS2 /WSe2 hetero-multilayers exhibited direct bandgap semiconductor characteristics with bandgap energy ( E g ) in a range of 0.45–0.55 eV at room temperature, very attractive for optoelectronics (wavelength range 2.5–2.75 μ m) based on thicker two-dimensional (2D) materials. It was also found that the interlayer distance has a significant impact on the electronic properties of the hetero-multilayers, for example a five orders of magnitude change in the conductance was observed. Three material phases, direct bandgap semiconductor, indirect bandgap semiconductor, and metal were observed in MoS2 /WSe2 hetero-multilayers, as the interlayer distance decreased from its relaxed (i.e., equilibrium) value of about 6.73 Å down to 5.50 Å, representing a vertical pressure of about 0.8 GPa for the bilayer and 1.5 GPa for the trilayer. Such new hybrid layered materials are very interesting for future nanoelectronic pressure sensor and nanophotonic applications. This study describes a new approach to explore and engineer the construction and application of tunable 2D semiconductors.